Assessment of IAAF Racewalk Judges' Ability to Detect Legal and Non-legal Technique - Hanley, Brian; Tucker, Catherine B.; Bissas, Athanassios (Frontiers in Sports and Active Living, 2019)
IAAF Rule 230.2 states that racewalkers must have no visible (to the human eye) loss of contact with the ground and that their advancing leg must be straightened from first contact with the ground until the “vertical upright position”. The aims of this study were first to analyze racewalking judges’ accuracy in assessing technique and, second, to measure flight times across a range of speeds to establish when athletes were likely to lose visible contact. Twenty racewalkers were recorded in a laboratory using a panning video camera (50 Hz), a high-speed camera (100 Hz) and three force plates (1000 Hz). Eighty-three judges of different IAAF Levels (and none) viewed the panned videos online and indicated whether each athlete was racewalking legally. Flight times shorter than 0.033 s were detected by fewer than 12.5% of judges, and thus indicated non-visible loss of contact. Flight times between 0.040 and 0.045 s were usually detected by no more than three out of eight judges. Very long flight times (≥ 0.060 s) were detected by nearly all judges. The results also showed that what judges generally considered straightened knees (> 177°) was close to a geometrically straight line. Within this inexact definition, IAAF World Championship-standard Level III judges were most accurate, being more likely to detect anatomically bent knees and less likely to indicate bent knees when they did not occur. For the second part, the men racewalked down a 45-m indoor track at 11, 12, 13, 14 and 15 km/h in a randomized order, whereas the women’s trials were at 10, 11, 12, 13 and 14 km/h. Flight times, measured using an OptoJump Next photocell system (1000 Hz), increased for the men from 0.015 s at 11 km/h to 0.040 s at 14 km/h and 0.044 s at 15 km/h, and for the women from 0.013 s at 10 km/h to 0.041 s at 13 km/h and 0.050 s at 14 km/h. For judging by the human eye, the threshold for avoiding visible loss of contact therefore occurred for most athletes at approximately 14 km/h for men and 13 km/h for women.